Tip 2 Diyabet Mellituslu Hastalarda HbA1c Konsantrasyon Düzeylerine Göre Serum Adropin Düzeyinin Belirlenmesi - Albayrak, Fatih; Uğur, Kader; Aydın, Süleyman (Gaziantep Islam Science and Technology University, 2025)
Amaç : Adropin son yıllarda keşfedilmiş ve glukoz ve lipid metabolizması ile ilişkili olduğu bildirilmiştir. Amacımız Tip 2 Diabetes Mellitus tanısı almış hasta grupları ile kontrol grubu arasında kan glikozile hemoglobin (HbA1c) konsantrasyon değerlerine göre kan serum adropin düzeyleri arasındaki ilişkiyi belirlemektir. Metod: Fırat Üniversitesi Hastanesi Endokrinoloji kliniğinden gözlem amaçlı 60 Tip 2 DM, 20 prediyabet hastası alındı. Ayrıca karşılaştırma için 20 sağlıklı birey normal kontrol grubu olarak alındı. Toplam 60 DM hastası HbA1c düzeylerine göre %9'dan büyük 20, %7-9 arasında 20 ve %7'den küçük 20 hasta olmak üzere 3 eşit gruba ayrıldı. Rutin kan testlerine ek olarak ELISA yöntemi ile adropin düzeyleri ölçüldü. Bulgular: DM'li hastaların serum adropin düzeyleri kontrol grubuna göre daha düşüktü (4,12±1,23 ng/mlversus 4,84±1,41 ng/ml, p%9 olan grubun adropin düzeyleri kontrol grubuna kıyasla daha düşüktü (3,23±1,14 ng/ml'ye karşı 4,84±1,41ng/ml, p < 0.001). Diyabetik hastalarda HbA1c ve adropin seviyeleri arasında negatif korelasyon tespit ettik (r=-0.377, p < 0.05). Sonuç: Bu çalışmada, adropin seviyelerinin artan HbA1c seviyeleri ile azaldığını bulduk. Kronik hipergliseminin veya zayıf kan şekeri regülasyonunun adropin seviyelerini düşürdüğü görülmektedir. Gelecekte, bu konuda daha fazla çalışmaya ihtiyaç vardır.

Purpose: Adropin is discovered in recent years and it has been reported to be associated with glucose and lipid metabolism . Our aim is to determine the relationship between blood serum adropin levels according to blood glycosylated hemoglobin (HbA1c) concentration values between the patient groups diagnosed with Type 2 Diabetes Mellitus and the control group. Methods: A total of 60 Type 2 DM, 20 prediabetes for observation were recruited from Endocrinology clinic of Fırat University Hospital. In addition, 20 healthy subjects were recruited for comparison as the normal control group. A total of 60 DM patients were divided into 3 equal groups according to HbA1c levels as 20 patients with HbA1c levels greater than 9 %, 20 between 7-9 %, 20 less than 7 %. In addition to routine blood tests, adropin levels were measured by ELISA method. Results: Patients with DM had lower serum adropin levels when compared with the controls (4,12±1,23 ng/mlversus 4,84±1,41 ng/ml, p 9% was lower in comparison with control group (3,23±1,14 ng/ml versus 4,84±1,41ng/ml, p < 0.001). In diabetic patients we determined negative correlation between HbA1c and adropin levels (r=-0.377, p < 0.05). Conclusion: In this study, we found that adropin levels were reduced with increasing levels of HbA1c. It appears that chronic hyperglycemia or poor blood sugar regulation lowers adropin levels. In the future, on this subject further studies are needed.
The Determination of serum Adropın level according to concentration levels of HbA1c in patients wıth Type 2 Diabetes Mellitus
Keywords: Endocrinology; Endokrinoloji